PERAN LEMBAGA UJIAN DALAM PEMBELAJARAN DAN PENGAKUAN KUALIFIKASI: STUDI KOMPARATIF CISCE DAN GAOKAO/NEEA - Arianda, Yoga Dwi; Nurcahya, Fikri; Ridwan, Achmad; Madani, Faisal; Suseno, Muchlas (Jurnal Administrasi Pendidikan Indonesia, 2025)
Assessment systems across countries often face challenges in balancing the functions of selection and learning. Examinations often focus on measuring learning outcomes without considering the accompanying pedagogical and social impacts. This study aims to critically analyze and compare the assessment systems implemented by the Council for the Indian School Certificate Examinations (CISCE) in India and the National Education Examinations Authority (NEEA)/Gaokao. This study uses a qualitative, comparative document analysis design to provide an in-depth understanding of the characteristics, principles, and implications of both institutions' assessment systems. The research subjects consisted of 32 official documents. Data were collected through documentation studies and in-depth interviews. The instrument was a validity analysis sheet containing four main components: content relevance, indicator clarity, source consistency, and theoretical relevance. Data analysis was conducted descriptively and analytically using thematic categorization techniques based on four main dimensions: assessment instrument development, system validity and reliability, impact on learning, and institutional credential recognition. The results show that the CISCE excels in curriculum flexibility, integration of formative assessment, and recognition of international credentials. In contrast, the Gaokao excels in mass selection efficiency and national standard consistency. This study concludes that an effective assessment system must balance selection and student potential development to avoid excessive academic pressure. The implications of this research emphasize the importance of developing a national assessment system that is equitable, relevant, and oriented toward lifelong learning